« Du champ des hommes »… - Cohen Hadria, Michèle (CV Photo)

(untitled) (Les Productions Ciel variable, 2002)
Abstract Manifesting her propensity for memory, Catherine Poncin takes no photographs; instead, she draws from a corpus of urban and community archives to gather significant, often unperceived "layers." In Bobigny, a Paris suburb, she proceeds to "pile up strata of clues," revealing the town's market-gardening activities, its memory of the Shoah, and its redevelopment into uniform neighbourhoods after the war. A reading by the sociologist-anthropologist Pierre Bourdieu throws light on certain prescriptions inherent to community photography. However, these prove to be absent in a population burdened by a hybrid urbanism, even in the search for an unanchored lived memory...